Analysis of the Influence of Capital Structure, Working Capital Turnover, and Profitability on Firm Value with Firm Size as a Moderating Variable (Industrials and Basic Materials Sector Listed on the IDX) - Putri Febrianti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the effect of capital structure, working capital turnover, and profitability on firm value with firm size as a moderating variable in the Industrials and Basic Materials sectors listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Using a quantitative approach and associative research type, this study employs secondary data through documentation techniques. The sampling method used is purposive sampling, with a final sample of 73 companies that consistently published sustainability reports. The analytical method used is Moderated Regression Analysis (MRA), preceded by classical assumption testing. The results indicate that capital structure, working capital turnover, and profitability each have a significant and negative effect on firm value. Additionally, firm size significantly moderates the relationship between working capital turnover and profitability on firm value but does not moderate the relationship between capital structure and firm value. The coefficient of determination (R²) shows that 91.4% of the variation in firm value can be explained by the variables in the model. These findings suggest that optimal capital structure, effective working capital management, and consistent profitability considering firm size are critical to sustaining firm value.